“Nossos livros foram discos": potencialidades pedagógicas do rap para a educação das relações étnico-raciais - Santos, Paulo Henrique Ferreira Borges dos (Universidade Federal de São Carlos, 2024)
This research presents the potentiality of rap for the education of ethnic-racial relations. It aims to understand rap as a culture elaborated from the intellectual production of the black diaspora, seeking to articulate it as a knowledge from which it is possible to outline it with school pedagogies. Thus, we aim, endorsing Law 10.639/03 and the guidelines of Opinion 003/2004 of the National Council of Education, to contribute to the elaboration of school practices that effectively contemplate the education of ethnic-racial relations. Methodologically, this research has as its corpus documentary analysis, interviews, bibliographic research, and rap works. As a political commitment, just as rap has historically emphasized, this research is a proposal for a political struggle response so that in the near future, lyrics like “I saw a little black boy / his notebook was a rifle” (Racionais MC's, 2002) are remembered just as elements of the past, and no longer as accounts of the lived experience of black people.
Our books were discs: pedagogical potentialities of rap for the education of ethnic-racial relations
Keywords: Rap; Educação; Lei 10.639/03; Rap; Education; Law 10.639/03; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM